2008
DOI: 10.1080/13623690701775171
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mental disorders and torture among Bhutanese refugees in Nepal: a systemic review and its policy implications

Abstract: The mass expulsion and exile of Bhutanese de facto refugees to displaced camps in Nepal represents one of the world's most neglected humanitarian crises. We aimed to summarize the impact of the long-term displacement on refugee mental illness using systematic review techniques, a methodology seldom used in the humanitarian field. In order to examine the impact among the population and the association between tortured refugees over non-tortured refugees, we searched 11 electronic databases from inception to 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 9 publications
0
22
0
2
Order By: Relevance
“…PTSD is highly comorbid with other psychiatric disorders and is associated with perceived psychosocial needs. A higher prevalence of mental health concerns were identified compared to similar studies among refugees in both pre and post-resettlement settings [28][29][30][31][32][33]. Two previous studies conducted in Nakivale found relatively high prevalence of PTSD, 61.7% among Congolese refugees and 48.1% among Somali refugees [17,34].…”
Section: Discussionmentioning
confidence: 70%
“…PTSD is highly comorbid with other psychiatric disorders and is associated with perceived psychosocial needs. A higher prevalence of mental health concerns were identified compared to similar studies among refugees in both pre and post-resettlement settings [28][29][30][31][32][33]. Two previous studies conducted in Nakivale found relatively high prevalence of PTSD, 61.7% among Congolese refugees and 48.1% among Somali refugees [17,34].…”
Section: Discussionmentioning
confidence: 70%
“…Although the mental health of Bhutanese refugees in Nepal has been studied previously, [27] no systematic investigation has focused on the mental health and suicide risks of Bhutanese refugees in the US. Between January 2008 and November 2014, more than 78,541 Bhutanese refugees were resettled to the US.…”
Section: Introductionmentioning
confidence: 99%
“…The full texts of the remaining 140 citations were evaluated, and 117 articles were excluded, which did not fulfill the eligibility criteria. Finally, 23 articles meeting all the criteria were recruited in this umbrella review (see Table 3), including 12 systematic reviews (Aggarwal and Berk, 2015;Arora and Aeri, 2019;Hossain et al, 2017Hossain et al, , 2014Math and Srinivasaraju, 2010;Mills et al, 2008;Mirza and Jenkins, 2004;Nadkarni et al, 2013;Naskar et al, 2017;Newman, 2013;Rajapakse et al, 2013;Thapa et al, 2018) and 11 meta-analyses (Chauhan et al, 2019;Ganguli, 2000;Hendrickson et al, 2019;Hussain et al, 2018;Mahendran et al, 2019;Malhotra and Patra, 2014;Pilania et al, 2019;Prabhu et al, 2019;Ranjan and Asthana, 2017;Reddy and Chandrashekar, 1998;Upadhyay et al, 2017).…”
Section: Resultsmentioning
confidence: 99%